Mathematical Modeling of Feelings in Viewpoint of Analysis of Olvido Poetry with Fractional Operators - Mustafa Ali Dokuyucu; Burak Armağan; Ülkü Eliuz; Ahmet Ocak Akdemir; Mehmet Emir Köksal (Journal of Mathematics)
The main motivation point of the article and the main factor that provides originality are an analysis of the modeling of feelings in the perspective of the analysis of Olvido’s poetry with the help of two fractional operators that offer the most effective solutions to real-world problems. In the study, first of all, the effect and contribution of fractional analysis to be applied and theoretical sciences were examined. A mathematical model of the feelings described in Olvido’s poem has been created to establish an important connection between fractional operators, which are an effective tool in the explanation of many physical and applied phenomena, and literary works that try to describe human life and feelings. The solutions of this model are investigated with the help of Caputo and Atangana–Baleanu fractional derivative operators. The findings were supported by various graphics in the light of special values of the parameters of the operators. The study focuses on generalizing the effects of literature research on human life to a general framework, not only providing the realization of the outputs that the literature field brings to human life and literature with the help of a mathematical model. The study has a rare content in the literature in terms of bringing together poetry and mathematics, which deal with human life with different methodologies.